Exploring Recent Advances in Dopaminergic Drug Therapy for Parkinson's Disease: Efficacy and Safety Profiles - 1. Allahwarayo kanhio 2. Manisha Lohana 3. Raja pawan 4. Hem Raj 5. Kheentesh kumar 6: Syed Fazil Ali 7. Sanjeet Kumar 8. Aanand Kumar Lohana 9. Pir Rafiullah Jan Sarhandi 10. Saqlain Ahmed 11. Zubair Ahmed 12. Ali karim (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by depletion of dopaminergic neurons, leading to motor and non-motor signs. Recent advancements in dopaminergic drug therapy have shown promise in managing these symptoms, yet the efficacy and safety profiles of these therapies require comprehensive evaluation.Aim: This research aimed to explore effectiveness and protection profiles of recent advances in dopaminergic drug therapy for Parkinson's disease.Methods: An overall of 300 patients detected having Parkinson's disease were included in this resaerch, conducted at Liaquat University of Medical and Health Sciences, Jamshoro, and Isra University, Hyderabad. The study spanned from May 2023 to October 2023. Patients were administered various dopaminergic therapies, and their responses were monitored through clinical evaluations, motor function assessments, and adverse event reporting. Data were analyzed to determine the efficacy and safety of these therapies.Results: The study observed significant improvements in motor function among patients receiving advanced dopaminergic therapies. The Unified Parkinson's Disease Rating Scale (UPDRS) scores demonstrated the marked decrease in motor signs. Furthermore, patient-reported results indicated enhanced quality of life. However, adverse effects such as dyskinesia and hallucinations were noted in a subset of patients, necessitating careful management and monitoring.Conclusion: Recent advances in dopaminergic drug therapy for Parkinson's disease were found to be effective in improving motor function and overall quality of life. Despite the noted adverse effects, these therapies presented a favorable benefit-risk ratio, underscoring their potential in PD management. Ongoing monitoring and individualized treatment approaches are recommended to optimize therapeutic outcomes